Serum Amyloid A Protein as a Potential Biomarker for Severity and Acute Outcome in Traumatic Brain Injury. (16th April 2019) - Wicker, Evan; Benton, Leah; George, Kershina; Furlow, William; Villapol, Sonia
Abstract : Traumatic brain injury (TBI) causes a wide variety of neuroinflammatory events. These neuroinflammatory events depend, to a greater extent, on the severity of the damage. Our previous studies have shown that the liver produces serum amyloid A (SAA) at high levels in the initial hours after controlled cortical impact (CCI) injury in mice. Clinical studies have reported detectable SAA in the plasma of brain injury patients, but it is not clear if SAA levels depend on TBI severity. To evaluate this question, we performed a mild to severe CCI injury in wild-type mice. We collected blood samples and brains at 1, 3, and 7 days after injury for protein detection by western blotting, enzyme-linked immunosorbent assay, or immunohistochemical analysis. Our results showed that severe CCI injury compared to mild CCI injury or sham mice caused an increased neuronal death, larger lesion volume, increased microglia/macrophage density, and augmented neutrophil infiltration. Furthermore, we found that the serum levels of SAA protein ascended in the blood in correlation with high neuroinflammatory and neurodegenerative responses. Altogether, these results suggest that serum SAA may be a novel neuroinflammation-based, and severity-dependent, biomarker for acute TBI.